FRI0450 PROBABILITY OF ACHIEVING LOW DISEASE ACTIVITY OR REMISSION IN SUBJECTS WITH ACTIVE PSORIATIC ARTHRITIS TREATED WITH APREMILAST. (June 2019) - Mease, Philip J.; Behrens, Frank; Gladman, Dafna D.; Kavanaugh, Arthur; Brunori, Michele; Teng, Lichen; Guerette, Benoit; Queiro, Ruben; Ogdie, Alexis
Abstract : Background: Therapeutic targets for long-term control of psoriatic arthritis (PsA) include the achievement of remission (REM) or low disease activity (LDA), as measured by the Clinical Disease Activity Index for Psoriatic Arthritis (cDAPSA). 1 Objectives: This post hoc analysis was conducted to (1) assess the predictive values of baseline clinical disease status on achieving long-term Clinical Disease Activity for Psoriatic Arthritis (cDAPSA) targets at Week 52 and (2) examine the association between early response to APR at Week 16 and the achievement of cDAPSA targets at Week 52. Methods: Pooled analyses of 3 phase III trials (PALACE 1-3) were performed among subjects assigned to receive APR 30 mg twice daily at baseline. Data were analyzed using multiple imputation to account for subjects who discontinued or had missing values, using all available cDAPSA scores. The probabilities of shifting across different cDAPSA categories from baseline or Week 16 responses to Week 52 were calculated within these subjects. Binary logistic regression was also performed to confirm the results. We also analyzed mean cDAPSA from baseline to Week 52 by cDAPSA category at Week 52 among subjects with moderate or high disease activity (HDA) at baseline. Results: A total of 494 subjects who received APR were included in the analyses; at baseline, 74.3% were in HDA, 24.5% in moderate disease activity, and 1.2% in LDA. Most subjects had ≥1 of the following conditions at baseline: affected body surface area ≥3%, dactylitis >0 based on the dactylitis severity score, enthesitis >0 based on the Maastricht Ankylosing Spondylitis Enthesitis Score or pre-existing axial PsA (physician determined) (HDA: 93.5%; moderate disease activity: 82.6%; LDA: 100%). The estimated probabilities of achieving either cDAPSA LDA or REM at Week 52 were 46.9% in subjects with baseline moderate disease activity (cDAPSA >13 to ≤27) and 71.1% in subjects with baseline LDA (cDAPSA >4 to ≤13) (Figure). In subjects with baseline HDA (cDAPSA >27), the probability of achieving LDA or REM by Week 52 was 24.9%. Subjects with moderate disease activity at baseline and improved to LDA or REM by Week 16 had high probabilities (58.9% and 88.5%) of remaining in target at Week 52. Among the subjects with moderate disease activity at baseline, a mean cDAPSA improvement of ≥30% by Week 16 was associated with achievement of LDA or REM at Week 52. Conclusion: Subjects with low or moderate disease activity at baseline exhibited the highest likelihood of achieving and maintaining an improvement in LDA or REM with continued APR treatment to Week 52. In these patients, a partial response with apremilast by Week 16 was associated with higher achievement or maintenance of cDAPSA LDA or REM by Week 52. References: [1] Smolen J, et al. Ann Rheum Dis. 2018;77:3-17. Disclosure of Interests: Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Frank Behrens Grant/research support from: AbbVie, Pfizer, Roche, Chugai, Prophylix, Bioline, Novartis, Consultant for: AbbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, Speakers bureau: Ad board: AbbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, Dafna D Gladman Grant/research support from: AbbVie, Amgen, Celgene, Lilly, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Galapagos, Gilead, Janssen, Lilly, Novartis, Pfizer, and UCB, Arthur Kavanaugh Grant/research support from: UCB Pharma, Michele Brunori Employee of: Celgene Corporation, Lichen Teng Employee of: Celgene Corporation, Benoit Guerette Employee of: Celgene Corporation, Ruben Queiro Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, BMS, Eli Lilly, Novartis, Pfizer, Takeda, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda